Analisis Biaya Produksi Dalam Meningkatkan Profitabilitas Perusahaan - Hidayat, Lukman; Halim, Suhandi (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Production cost is important in determining selling price and as a basis for management decision making to decide whether products manufacturing will be continued or discontinued. In addition, production cost has influence on firm’s profitability level; the smaller production cost, it will be inversely in proportion to its profitability. The purpose of this study is to see how far the role of production cost affects profitability. By making some adjustments in production cost such as making efficiency, total number of the company’s profitability can be increased compared to production cost which is still high. The research done at PT Sakti Kandakawana, located in Bogor. The result shows that PT Sakti Kandakawana is still be able to improve profitability by making some corrections on productionn cost. The assumption is the same number of selling will get higher profitability if it’s used lower production cost. Due to ineffective cost decreases more and more, the company has fund by efficiency without affecting products quality. Based on the evaluation, it shows that the production cost applied so far is still wasteful caused by raw materials used are expensive. In addition, it appears that cost for overtime work is not effective campare to cost for regular work. Thereby, when more efficient production cost is determined, the company’s profitability can be increased. Keywords:Production Cost; Company’s Profitability